Reflections on Certain Principles That May Guide a New Commentary (Tafsir) of the Qur’an - Tarif Khalidi (Religions, 2021)
The author starts from his experience as a translator of the Qur’an to argue on the need for a new commentary. The aim of such a new approach would be to convey a vision of Islam more in tune with Islamic history. Further, this is also needed in relation to the substantial Muslim communities living outside of the Muslim world. Antecedents are important in this and especially those coming from the so-called literary moment in the 20th-century Qur’an commentary tradition. A new commentary should be conducted by a committee. Additionally, the second part of the paper explores this possibility and what this committee should take care of in this direction, such as gender-consciousness or environment questions.